2010
DOI: 10.1016/s0140-6736(10)60954-3
|View full text |Cite|
|
Sign up to set email alerts
|

Vertebroplasty versus conservative treatment in acute osteoporotic vertebral compression fractures (Vertos II): an open-label randomised trial

Abstract: ZonMw; COOK Medical.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
633
6
9

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 773 publications
(691 citation statements)
references
References 26 publications
23
633
6
9
Order By: Relevance
“…Further randomized studies are needed to address this issue, although a subsequently published RCT (VERTOS II) found clear superiority of VP versus NSM [41]. The current study represents an updated systematic review of prospective studies of VAP and NSM for the treatment of osteoporotic VCFs.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Further randomized studies are needed to address this issue, although a subsequently published RCT (VERTOS II) found clear superiority of VP versus NSM [41]. The current study represents an updated systematic review of prospective studies of VAP and NSM for the treatment of osteoporotic VCFs.…”
Section: Discussionmentioning
confidence: 91%
“…Here, we report the comparison between RCTs-only. Seven randomized trials were recognized: one between BKP/VP (Liu [40]), one comparing BKP to NSM (Wardlaw [8]) and five comparing VP either to NSM (Rousing [20], Voormolen [9], Klazen [41]) or to SHAM procedure (Buchbinder [22], Kallmes [21]). In terms of disability reduction, there was no difference between BKP/VP (P = 0.16) or VP/NSM (P = 0.1), with BKP showing a trend toward greater improvement than conservative management (P = 0.078).…”
Section: Analysis Of Pooled Treatment Armsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, KP also aims to restore the height of the vertebral bodies. Recently, two randomized controlled trials (RCTs) have indicated that both of the procedures can produce immediate pain relief than conservative treatments [19,47]. In 2011, an RCT with 24 months of follow-up reported that kyphoplasty reduced pain and improved function, disability and quality of life more effectively than nonsurgical therapy without increasing the risk of additional vertebral fractures [8].…”
Section: Introductionmentioning
confidence: 99%
“…Sixteen percent of women after menopause and 20 % of all adults older than age 70 years suffer from vertebral compression fractures [1].The main complication of VCF is acute pain, reported in up to 84 % of patients with radiographic evidence of a compression fracture [2]. Vertebroplasty and kyphoplasty vertebral augmentation procedures have been shown to be more effective than conservative treatment when treating painful vertebral compression fractures [3,4].…”
Section: Introductionmentioning
confidence: 99%